Discipline among employee at Sunway Resort Hotel & Spa / Fatimah Krishna Murthey - Krishna Murthey, Fatimah (2015)
It is agreeable that discipline is essential in every aspect of life. It is equally essential in industrial undertakings. It implies the absence of chaos, irregularity and confusion in the behavior of workers. Workers in any organization need something to keep them working. The objectives of this study is to identify the rate for the disciplinary problems in Engineering Department, to measure what are factors that contributing to this problem, to analyze the impact of employee disciplinary problems on company performance and to recommends the solutions to overcome this problem. For the purpose of this study, employee of Engineering Department comprises of 43 operation staff were selected. The survey forms comprising of two sections, Section A of the survey form comprises of the personal information of the employees. Section B comprises questions which use to measure the employees satisfaction and attitude at workplace. 81 percent of the employee from Engineering Department was invited to participate in this research. Based on the study, the Engineering Department employee ranked good wages the most important satisfaction factor, and followed by promotion and growth in the organization, good relationship with immediate superior and co-workers, proper work schedule, communication and teamwork, full appreciation of work done, career development and advancement opportunities, interesting work and good working conditions. Therefore, the findings from the this study may allow the management to have better undertaking the existing problem and improve the performance of employees.